2010
DOI: 10.1673/031.010.2701
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Hilltopping in Thick-Headed Flies (Diptera: Conopidae)

Abstract: Direct observations of hilltopping behaviour in the thick-headed flies (Diptera: Conopidae) have only been mentioned once in the literature. Hilltop collecting, however, may be an effective way to survey these endparasitoids. The first evidence of hilltopping in species belonging to the subfamilies Myopinae and Dalmanniinae is presented and discussed. Field observations were conducted on Colle Vescovo, Italy and Mount Rigaud, Canada, and museum specimens were examined. Observations and records indicate that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…While species of Diptera, including Muscidae, Calliphoridae, and even other Conopidae, have been suggested as hosts to species of Stylogaster , this has not been confirmed by rearing experiments. A recent review of hilltopping mating behaviour in Conopidae (Mei et al., 2010) found that select species of all subfamilies, except Stylogastrinae, have been observed hilltopping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While species of Diptera, including Muscidae, Calliphoridae, and even other Conopidae, have been suggested as hosts to species of Stylogaster , this has not been confirmed by rearing experiments. A recent review of hilltopping mating behaviour in Conopidae (Mei et al., 2010) found that select species of all subfamilies, except Stylogastrinae, have been observed hilltopping.…”
Section: Discussionmentioning
confidence: 99%
“…Species of Conopidae have been the subject of much biological research with regards to host–parasite relationships (Schmid‐Hempel, 2001; Otterstatter, 2004), mimicry (Waldbauer, 1988) and hilltopping mating behaviour (Mei et al., 2010). There have also been a great number of taxonomic revisions of various groups of Conopidae (Kröber, 1939; Camras, 1996).…”
Section: List Of Taxa Included In the Analysis With Genbank Accessionmentioning
confidence: 99%
“…Waldbauer, ), and hilltopping mating behaviour (e.g. Mei, Gibson & Skevington, ). Little research has been conducted on the phylogenetic relationships between members of Conopidae.…”
Section: Introductionmentioning
confidence: 99%